Impact of COVID-19 on Employees' Performance : A Case Study on a German Company - Vaverka, Martin; de Batz de Trenquelléon, Laure Sabine Marie; Zezula, Jakub; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
The COVID-19 pandemic caused tremendous disruption across industries globally, with manufacturing suffering most. This thesis addresses this crsis, considering how the pandemic affected organisational resilience and workers' performance at KSB – a global manufacturer with a Czech subsidiary. The thesis uses a longitudinal case study with an analysis of 2019– 2023 sales documents, financial performance measures, and workers' engagement questionnaires. The research has a triple scope: on how employees' performance was affected by hybrid modes of work, how business continuity was enabled by digital transformation, and how KSB transformed its strategy during and in response to the pandemic. The data reveals that despite COVID-19 disruption in client cancellations and supply chain interruption, the business managed to keep performance intact with digital tools, hybrid forms of organization, and wise reappropriation of budgets. Insights at the selling level reveal a high level of volatility, resilience, and flexibility. Employee satisfaction levels increased postpandemia with increased flexibility, though cybersecurity risk remains an upcoming challenge. In accordance with research, flexible leadership and digital readiness weathered out the pandemic, with key takeaways for similarly industrial companies threatened by future disruption.
Vedoucí práce: Laure Sabine Marie de Batz de Trenquelléon
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses